Sinkronisasi Perencanaan Tata Ruang Daerah dengan Pembangunan Jalan Tol Berbasis Sustainable Development - Nurristi, Dinartika Arneda; Sarwono, Sarwono; Nuh, Mohammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
This study describes the synchronization of spatial planning with the construction of toll road-based sustainable development in the Area of Interchange Tol Madiun. Aimed to explore the information from some source: BAPPEDA Kabupaten Madiun, Dinas PUPR Kabupaten Madiun, Office of the Bagi Village, and Communities around the Interchange Tol Madiun. The results showed that; first, the synchronization of spatial planning with the construction of the Madiun toll road not fully following the RT/RW (community association) plan and unable to be categorized as ideal planning. The application of the participation has been running well, but there is still a discrepancy on the principle of continuity and holistically. Second, the implementation of Sustainable Development in the construction of the toll road is not running balance between economic development, social and environmental. Supporting factor form is the strong legal basis and the high level of community participation. Inhibiting factors in the form of rationalization of the budget because of the pandemic Covid19 and the lack of personals resource that is pure has graduated in spatial studies.